2020
DOI: 10.3802/jgo.2020.31.e94
|View full text |Cite
|
Sign up to set email alerts
|

The post-progression survival of patients with recurrent or persistent ovarian clear cell carcinoma: results from a randomized phase III study in JGOG3017/GCIG

Abstract: Objective In this study we sought to investigate the clinical factors that affect post-progression survival (PPS) in patients with recurrent or persistent clear cell carcinoma (CCC). We utilized the JGOG3017/Gynecological Cancer InterGroup data to compare paclitaxel plus carboplatin (TC) and irinotecan plus cisplatin (CPT-P) in the treatment of stages I to IV CCC. Methods We enrolled 166 patients with recurrent or persistent CCC and assessed the impact of variables, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Post-recurrence survival in this study was 13.96 months. Previous studies reported median post-recurrence survivals of 14.0–16.5 months [ 11 , 19 , 23 ]. Platinum sensitivity and primary stage were reported as independent prognostic factors for recurrent or persistent CCC, whereas chemotherapy regimens (paclitaxel plus carboplatin versus irinotecan plus cisplatin) did not demonstrate a significant difference [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Post-recurrence survival in this study was 13.96 months. Previous studies reported median post-recurrence survivals of 14.0–16.5 months [ 11 , 19 , 23 ]. Platinum sensitivity and primary stage were reported as independent prognostic factors for recurrent or persistent CCC, whereas chemotherapy regimens (paclitaxel plus carboplatin versus irinotecan plus cisplatin) did not demonstrate a significant difference [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported median post-recurrence survivals of 14.0–16.5 months [ 11 , 19 , 23 ]. Platinum sensitivity and primary stage were reported as independent prognostic factors for recurrent or persistent CCC, whereas chemotherapy regimens (paclitaxel plus carboplatin versus irinotecan plus cisplatin) did not demonstrate a significant difference [ 23 ]. Our investigations revealed that single-site and nodal site recurrences indicated a favorable prognosis for post-recurrence survival.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For relapsed EOC, grading platinum sensitivity by the distribution of 6- and 12-month progression-free intervals (PFI) has been adopted in clinical guidelines, and is relevant to the selection of second-line regimens [ 20 , 21 , 22 ]. Owing to the chemo-resistant features of OCCC, individualized PFI criteria (i.e., PFI extended to 12 and 18 months) have been proposed [ 21 ].…”
Section: Introductionmentioning
confidence: 99%